Diagnostic Accuracy of First Trimester Hyperuricemia for Prediction of Subsequent Gestational Diabetes Mellitus - Aiza Rehman, Sardar Umer Rehman, Rabia Sarwar, Muhammad Ayub, Ayesha Masood (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Gestational diabetes mellitus (GDM) is a condition in which pregnant females develop. GDM causes significant and often potentially maternal and fetal complications. Uric acid is the end product of purine metabolism. Recent literature suggests a bidirectional causal relationship between hyperuricemia and insulin resistance. So we conducted this study. Objective: To find diagnostic accuracy of first trimester hyperuricemia for prediction of subsequent gestational diabetes mellitus confirmed on oral glucose tolerance test. Methods: This was a Cross-sectional study conducted at Department of Obstetrics and Gynecology CMH Lahore during time duration 25-4-2017 to 24-10-2017. All females met inclusion criteria were enrolled in this study. Blood samples in first trimester were collected for analysis of serum uric acid. Then after 26-28 weeks of gestation, OGTT was done and presence of GDM was recorded. All the data was collected on proforma. SPSS version 22 was used for data entry and analysis. A 2 x 2 table was generated find the diagnostic accuracy of hyperuricemia taking OGTT as gold standard. Results: The mean age of females was 26.70±5.21years. The mean height, weight and BMI of females were 1.62±0.07m, 61.07±8.54kg and 23.32±3.72kg/m2. The mean gestational age of females was 9.96±.37weeks at time of enrolment in the study. The mean uric acid level at time of presentation was 4.43±3.61mg/dl. In this study, the sensitivity and specificity of hyperuricemia for prediction of GDM were 91.1% and 95.7%. The PPV and NPV of hyperuricemia were 86.8% and 97.2%. The overall diagnostic accuracy was 94.5%. Conclusion: Thus the accuracy of hyperuricemia was high and it is now accepted as reliable marker for prediction of GDM in later pregnancy. Keywords: Diagnostic accuracy, first trimester, hyperuricemia, gestational diabetes mellitus, oral glucose tolerance test, uric acid